Epidemiological study of cholera in Qazvin city during summer of 2011 - Ashrafi Hafez, Asghar; Ranjbaran, Mehdi; Modabber, Mohammad Reza; Mosavi-Jarrahi, Alireza; Khooban, Hasan; Rezaei, Ahmad; Imanzad, Masoumeh (Archives of Advances in Biosciences, 2013)
Cholera is an acute intestinal infection caused by consuming food or water contaminated with the bacterium Vibrio cholerae. Two main epidemiological characteristic of disease is tendency for create of sudden outbreaks and the ability to causing a pandemic. The objective of this study is to describe the epidemiology of the disease. This survey is a descriptive cross-sectional study based on reports from the health centers and hospitals covered by city health centers. Rectal swab is obtained from all suspected cases. After reporting each positive case, health team was sent to the location and it completed the epidemiological form. Data were analyzed by version 16 of SPSS software. All reported patients were 44 cases. Epidemic lasted from 4 August to 18 September 2011. Ogawa was the predominant pathogenic serosubtype. 47.7% of all patients admitted to the hospital and 52.3% were treated as outpatients. Most of the patients were in age group >60 years and there were no reports of disease in age group under 15 years. 2 of the 44 patients had mild symptoms of diarrhea, 13 patients had moderate and 29 cases had severe diarrhea. Not affection of age groups less than 15 years indicates epidemic patterns of disease in the city. Severity of symptoms is important in case finding; then, in disease surveillance system we should obtain rectal swab specimen from all cases of diarrhea with severe symptoms.